2021
DOI: 10.1088/1755-1315/939/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Optimal Parameters of the Jet Aeration

Abstract: To ensure effective aeration of the biological wastewater treatment process, easy-to-operate and not too energy-intensive units are needed. Jet aerators have such capabilities. In this study, the authors searched for the best hole shape for the aeration nozzles. It was determined that a nozzle with an elongated hole has the largest size of the actively aerated zone. Experimental studies of nozzles of a diameter of 56 mm with nozzles of elongated shape showed that the best characteristics of mass transfer are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In the case of an approach pipe ending with a nozzle, Figure 1, which has a known assumed loss coefficient, the head loss as associated with the high issuing velocity head and is therefore not as minor loss. But, in the present study, it is suggested that the minor loss of the nozzle may be expressed in terms of the equivalent length of approach pipe (Le), that has the same head loss for the same discharge delivered from the nozzle De Cock (2017), Radkevich et al (2021) Where F = friction factor of approach pipe, Le = equivalent length of pipe, VP = velocity of flow in approach pipe, D = diameter of approach pipe, g = acceleration of gravity, K = loss coefficient of minor loss due to nozzle, VJ = absolute velocity of the jet, and d = diameter of nozzle opening (diameter of jet).…”
Section: Minor Nozzle Lossmentioning
confidence: 82%
“…In the case of an approach pipe ending with a nozzle, Figure 1, which has a known assumed loss coefficient, the head loss as associated with the high issuing velocity head and is therefore not as minor loss. But, in the present study, it is suggested that the minor loss of the nozzle may be expressed in terms of the equivalent length of approach pipe (Le), that has the same head loss for the same discharge delivered from the nozzle De Cock (2017), Radkevich et al (2021) Where F = friction factor of approach pipe, Le = equivalent length of pipe, VP = velocity of flow in approach pipe, D = diameter of approach pipe, g = acceleration of gravity, K = loss coefficient of minor loss due to nozzle, VJ = absolute velocity of the jet, and d = diameter of nozzle opening (diameter of jet).…”
Section: Minor Nozzle Lossmentioning
confidence: 82%
“…To ensure that the biological wastewater treatment process is effectively aerated, simple basic units are needed. Jet aerators provide these characteristics . Also, compared to conventional systems, the oxygen exchange mechanism using a sputtering jet of water is a better way to add oxygen to a pool of water .…”
Section: Introductionmentioning
confidence: 99%
“…Jet aerators provide these characteristics. 12 Also, compared to conventional systems, the oxygen exchange mechanism using a sputtering jet of water is a better way to add oxygen to a pool of water. 13 Additional uses include cell bioreactor, oxygenation, and mineral-processing flotation cells.…”
Section: Introductionmentioning
confidence: 99%